ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT DI KECAMATAN KASIMBAR KABUPATEN PARIGI MOUTONG (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This research aims to determine the income of oil palm farmers in Kasimbar District, Parigi Moutong Regency. This research was conducted in Kasimbar District, Parigi Moutong Regency. The location of this research was chosen intentionally (Purposive) with the consideration that Kasimbar Subdistrict is an area where palm oil production is greater than other subdistricts in Parigi Moutong Regency. This research was conducted from October to November 2019. The population in this study were all oil palm farmers in Kasimbar District. Based on the initial survey, it was found that the total population of oil palm farmers was 102 people. The sample was determined by using the simple random sampling method (Simple Random Sampling), the number of samples taken was 31 people. The analysis used is income analysis. The analysis showed that the average production was 77.132.23 kg of oil/ 3,19ha/year or 24.152.52/ha/ year. The selling price of local palm oil is Rp. 700.00/kg, so the average income received by oil palm farmers is Rp. 53.992.561/3.19ha/ year or Rp. 16.906,761/ha/year. The average total cost incurred by farmers is IDR 16.484.534/3.19 ha/year, or IDR 5.161.824/ha/year, so it is known that the average income of oil palm farmers is IDR 37.508.024/3,19 ha/year, or Rp. 11.744.937/ ha/ year.